Information and functional component of the functions system of the Verkhovna Rada of Ukraine apparatus as the main indicator of its constitutional-legal status - Погребняк, Н. С. (Problems of legality, 2014)
The article is devoted to the research of the information function realization by the Verkhovna Rada of Ukraine apparatus as a component in the system of it constitutional-legal status with the use of the applied knowledges of the information law philosophy. The critical analysis of the information support of the lawmaking activity of the Verkhovna Rada of Ukraine has been made. The conceptual positions have been formulated, new recommendations and conclusions as to the investigated problems have been given grounds.